ASSISTANCE TO STRENGTHEN BUSINESS ORGANIZATIONAL GOVERNANCE AND FINANCIAL REPORTING TOWARDS A SUSTAINABLE COOPERATIVE BUSINESS PROCESS - Achmad Murdiono; Fadia Zen; Lulu Nurul Istanti (Transpublika Publisher, 2024)
Regency Blitar is one of the districts in East Java province with a high number of SMEs. One sector that is growing rapidly in this area is cooperative production. Cooperatives with production business units have the potential to become key drivers of economic growth on a small scale in the Blitar Regency. However, despite the high potential for business development through cooperatives, the progress of business unit growth under cooperative management is still classified as low. Based on the analysis of this activity, several problems were identified: 1) The majority of cooperatives are developing business units without conducting feasibility analyses, making them very vulnerable to business failure. 2) Cooperative managers lack the ability to diversify their businesses. 3) The cooperative administrators' abilities in financial management and reporting are still low. This activity began with introductory activities that included a literature review, followed by field studies through secondary data. The next stage involved an internal Focus Group Discussion (FGD) aimed at identifying the real conditions of cooperatives in the field, conducted with the Blitar Regency Cooperatives and MSMEs Service. To ensure the smooth running of the activities, the executing team coordinated with the partner institution, namely the Blitar Regency Cooperatives and MSMEs Service, which is the official government body responsible for fostering cooperatives.